2005
DOI: 10.1128/jb.187.15.5318-5329.2005
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Develops an Alternative, ica- Independent Biofilm in the Absence of the arlRS Two-Component System

Abstract: The biofilm formation capacity of Staphylococcus aureus clinical isolates is considered an important virulence factor for the establishment of chronic infections. Environmental conditions affect the biofilm formation capacity of S. aureus, indicating the existence of positive and negative regulators of the process. The majority of the screening procedures for identifying genes involved in biofilm development have been focused on genes whose presence is essential for the process. In this report, we have used ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
170
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(182 citation statements)
references
References 52 publications
(52 reference statements)
6
170
1
5
Order By: Relevance
“…Furthermore, the detachment results indicate that ß-1,6-linked polysaccharides are probably not the major matrix component of PIA-independent biofilms. PIA-independent biofilm formation has also been reported in S. epidermidis, S. aureus, and S. lugdunensis (15,18,41,43,46). Only two isolates in our study showed Ͼ75% detachment when they were treated with NaIO 4 , which is comparable to the level of detachment observed for S. epidermidis RP62A (43).…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, the detachment results indicate that ß-1,6-linked polysaccharides are probably not the major matrix component of PIA-independent biofilms. PIA-independent biofilm formation has also been reported in S. epidermidis, S. aureus, and S. lugdunensis (15,18,41,43,46). Only two isolates in our study showed Ͼ75% detachment when they were treated with NaIO 4 , which is comparable to the level of detachment observed for S. epidermidis RP62A (43).…”
Section: Discussionsupporting
confidence: 73%
“…It has been recently reported that insertional mutation of either yhcS or yhcR has no effect on the viability of S. aureus (37). This contradictory result may be due to the functional untruncated proteins generated from the insertional knockout mutants.…”
mentioning
confidence: 65%
“…As a result, agr-dysfunctional strains have a tendency to form biofilms in vitro, which has been attributed to, among other factors, the decreased production of proteases responsible for digestion of biofilm extracellular matrix, overexpression of protein A and the increased accumulation of fibronectin-binding proteins (Toledo-Arana et al, 2005;Merino et al, 2009;Vergara-Irigaray et al, 2009;Ferreira et al, 2013). The literature differs as regards the association between the type of agr and biofilm production (Cafiso et al, 2007;Lim et al, 2013).…”
Section: Discussionmentioning
confidence: 96%